Contemporary ecotypic divergence during a recent range expansion was facilitated by adaptive introgression. (16th September 2014) - Lucek, K.; Lemoine, M.; Seehausen, O.
Abstract Although rapid phenotypic evolution during range expansion associated with colonization of contrasting habitats has been documented in several taxa, the evolutionary mechanisms that underlie such phenotypic divergence have less often been investigated. A strong candidate for rapid ecotype formation within an invaded range is the three‐spine stickleback in the Lake Geneva region of central Europe. Since its introduction only about 140 years ago, it has undergone a significant expansion of its range and its niche, now forming phenotypically differentiated parapatric ecotypes that occupy either the pelagic zone of the large lake or small inlet streams, respectively. By comparing museum collections from different times with contemporary population samples, we here reconstruct the evolution of parapatric phenotypic divergence through time. Using genetic data from modern samples, we infer the underlying invasion history. We find that parapatric habitat‐dependent phenotypic divergence between the lake and stream was already present in the first half of the twentieth century, but the magnitude of differentiation increased through time, particularly in antipredator defence traits. This suggests that divergent selection between the habitats occurred and was stable through much of the time since colonization. Recently, increased phenotypic differentiation in antipredator defence traits likely results from habitat‐dependent selection on alleles that arrived through introgression from a distantly related lineage from outside the Lake Geneva region. This illustrates how hybridization can quickly promote phenotypic divergence in a system where adaptation from standing genetic variation was constrained.